2017
DOI: 10.1097/gme.0000000000000931
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with different symptom domains among postmenopausal Saudi women in Riyadh, Saudi Arabia

Abstract: Establishing educational and counseling programs for postmenopausal women, their spouses, and other family members could improve social support and hence quality of life of postmenopausal women. Effective preventive strategies to deal with modifiable risk factors, such as obesity and work stress, should also be implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Menopause is the permanent cessation of menstruation for at least 1 year after the last menstruation without other reasons, such as chemotherapy, gland disorders, and removal of the uterus ( 1 ). Menopause is characterized by a wide range of psychological and physiological symptoms, including urogenital manifestations (sexual problems and urinary incontinence), somatic manifestations (heart discomfort, hot flashes, and sleeping difficulties), and psychological manifestations (distress, mood swings, and anxiety), all of these symptoms influence women's general wellbeing and reducing the quality of life ( 2 , 3 ). The prevalence of postmenopausal symptoms can be influenced by socio-demographic, psychosocial, cultural, and lifestyle factors, which differ markedly among women all over the world ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Menopause is the permanent cessation of menstruation for at least 1 year after the last menstruation without other reasons, such as chemotherapy, gland disorders, and removal of the uterus ( 1 ). Menopause is characterized by a wide range of psychological and physiological symptoms, including urogenital manifestations (sexual problems and urinary incontinence), somatic manifestations (heart discomfort, hot flashes, and sleeping difficulties), and psychological manifestations (distress, mood swings, and anxiety), all of these symptoms influence women's general wellbeing and reducing the quality of life ( 2 , 3 ). The prevalence of postmenopausal symptoms can be influenced by socio-demographic, psychosocial, cultural, and lifestyle factors, which differ markedly among women all over the world ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi society, the collective culture prevails, with the majority of support coming from the mother, sisters, aunts, and even the extended family, especially for young women. This culture may reflect the level of trust and comfort which exists between family members (AlQuaiz et al, 2017). The woman has the right to ask for emotional or tangible support, and it is the responsibility and social obligation of the rest of the family to provide it.…”
Section: Discussionmentioning
confidence: 99%
“…The research on social support in Saudi Arabia is in its preliminary stages. Studies have measured social support in the context of menopausal aged women and found that a lack of emotional and tangible support was associated with poor quality of life (AlQuaiz et al, 2017). Although the local culture and traditions emphasize social relationships, still, there is a significant percentage of women with inadequate or lack of support (Abdel-Khalek et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…11,12 MENQOL questionnaire is a validated instrument used to measure health-related quality of life in middle-aged women in the years beyond the onset of menopause. It consists of 29 items grouped into four domains: vasomotor (1-3), psychosocial (4-10), physical (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) and sexual (27-29) [8][9][10] . For frequency of the MENQOL symptoms, participants were asked to rate whether they had experienced the symptom in the past month.…”
Section: Data Collection Instrumentmentioning
confidence: 99%